Treatment of Acquired Digital Arteriovenous Malformation with Progression during Pregnancy. Issue 12 (December 2019) - Fujimaki, Hiroshi; Takeuchi, Masaki
Abstract : Summary: Acquired digital arteriovenous malformation (AVM) is a relatively rare form of AVM that occurs in the fingers. Together with a review of the literature, we report a rare case of acquired digital AVM that enlarged after pregnancy. The patient was a 32-year-old woman with the chief complaint of digital swelling accompanied by a burning sensation. During her pregnancy, the swelling of the fingers recurred, with a symptom of throbbing sensation. After giving birth, the swelling reduced but did not completely disappear. At the first visit, we observed purple discoloration and swelling of the ulnar aspect of the proximal interphalangeal joints of the left hand. Contrast-enhanced computed tomography scanning via the digital arteries of the left hand revealed a lesion showing early venous return, leading to the diagnosis of AVM. Surgery was performed under general anesthesia. The digital artery supplying the lesion was identified and dissected under a surgical microscope. At 15 months after surgery, there was no recurrence, sensory dysfunction, or mobility impairment.